2015
DOI: 10.1099/mic.0.000177
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous complementation studies in Escherichia coli with the Hyp accessory protein machinery from Chloroflexi provide insight into [NiFe]-hydrogenase large subunit recognition by the HypC protein family

Abstract: Six Hyp maturation proteins (HypABCDEF) are conserved in micro-organisms that synthesize [NiFe]-hydrogenases (Hyd). Of these, the HypC chaperones interact directly with the apo-form of the catalytically active large subunit of Hyd enzymes and are believed to transfer the Fe(CN) 2 CO moiety of the bimetallic cofactor from the Hyp machinery to this large subunit. In E. coli, HypC is specifically required for maturation of Hyd-3 while its paralogue, HybG, is specifically required for Hyd-2 maturation; either HypC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 68 publications
4
29
0
Order By: Relevance
“…Importantly, these truncated variants of HypC retained their ability to mature Hyd-1 and Hyd-3. This finding also explains why the short (71 amino acids) HypC from D. mccartyi, when heterologously produced in the E. coli hypChybG double-null mutant SSH228, showed promiscuous maturation behaviour in that it was able to mature all 3 E. coli enzymes [Hartwig et al, 2015]. A C-terminal extension on the HypC orthologue, HupF, which co-exists with HypC in the cells of the symbiotic nitrogen-fixing bacterium Rhizobium leguminosarum, has been shown to stabilize maturation of the target hydrogenase large subunit towards oxygen [Albareda et al, 2012], suggesting that modification or extension of the C-terminus can add functional specificity to these chaperones.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Importantly, these truncated variants of HypC retained their ability to mature Hyd-1 and Hyd-3. This finding also explains why the short (71 amino acids) HypC from D. mccartyi, when heterologously produced in the E. coli hypChybG double-null mutant SSH228, showed promiscuous maturation behaviour in that it was able to mature all 3 E. coli enzymes [Hartwig et al, 2015]. A C-terminal extension on the HypC orthologue, HupF, which co-exists with HypC in the cells of the symbiotic nitrogen-fixing bacterium Rhizobium leguminosarum, has been shown to stabilize maturation of the target hydrogenase large subunit towards oxygen [Albareda et al, 2012], suggesting that modification or extension of the C-terminus can add functional specificity to these chaperones.…”
Section: Discussionmentioning
confidence: 51%
“…2a), highlights the 3 variable regions, VR1 (amino acids 13-18 with reference to HypC Ec ), VR2 (33-43), and VR3 (75-90); the amino acid range of VR1 and of VR3 has been restricted somewhat compared to the previous definition [Hartwig et al, 2015]. The solution structure of HypC from E. coli has been determined [Wang et al, 2007] and the locations of VR1, VR2, and VR3 in the protein are shown in Fig.…”
Section: Hypc Determinants Important For the Recognition Of Hycementioning
confidence: 99%
See 3 more Smart Citations